ZebraZoom: an automated program for high-throughput behavioral analysis and categorization - Mirat, Olivier; Sternberg, Jenna R.; Severi, Kristen E.; Wyart, Claire (Frontiers in Neural Circuits, 2013)
The zebrafish larva stands out as an emergent model organism for translational studies involving gene or drug screening thanks to its size, genetics, and permeability. At the larval stage, locomotion occurs in short episodes punctuated by periods of rest. Although phenotyping behavior is a key component of large-scale screens, it has not yet been automated in this model system. We developed ZebraZoom, a program to automatically track larvae and identify maneuvers for many animals performing discrete movements. Our program detects each episodic movement and extracts large-scale statistics on motor patterns to produce a quantification of the locomotor repertoire. We used ZebraZoom to identify motor defects induced by a glycinergic receptor antagonist. The analysis of the blind mutant atoh7 (lak) revealed small locomotor defects associated with the mutation. Using multiclass supervised machine learning, ZebraZoom categorizes all episodes of movement for each larva into one of three possible maneuvers: slow forward swim, routine turn, and escape. ZebraZoom reached 91% accuracy for categorization of stereotypical maneuvers that four independent experimenters unanimously identified. For all maneuvers in the data set, ZebraZoom agreed 73.2-82.5% of cases with four independent experimenters. We modeled the series of maneuvers performed by larvae as Markov chains and observed that larvae often repeated the same maneuvers within a group. When analyzing subsequent maneuvers performed by different larvae, we found that larva-larva interactions occurred as series of escapes. Overall, ZebraZoom reaches the level of precision found in manual analysis but accomplishes tasks in a high-throughput format necessary for large screens.